Kinetics of soil chemical processes - Sparks, Donald L., 1953- (Academic Press, 1989)
The kinetics of reactions in soil and aquatic environments is a topic of extreme importance and interest. To properly understand the fate of applied fertilizers, pesticides, and organic pollutants with time, and to thus improve nutrient availability and the quality of our groundwater, one must study kinetics. This is the first compreKey Features* Demonstrates different kinetic methodologies* Shows how reactions on soil and soil constituents can be measured by utilizing different techniques* Describes rates and mechanisms of interactions with pesticides and organic pollutants with soil* Covers.